Modeling and Analysis of SOGI-PLL/FLL-Based Synchronization Units: Stability Impacts of Different Frequency-Feedback Paths - Zhang, Chen; Foyen, Sjur; Suul, Jon Are; Molinas, Marta (IEEE transactions on energy conversion, 2021)
Second-order Generalized Integrator (SOGI)-based quadrature-signal-generator (QSG) together with either a phase-locked-loop (PLL) or a frequency-locked-loop (FLL) constitute two types of typical synchronization units (i.e., SOGI-PLL and -FLL) that have been widely used in grid-tied converter systems. This article will reveal and clarify the stability issue of these two synchronization units arising from different implementations of the frequency-feedback-path (FFP) connecting the SOGI-QSG and the PLL/FLL. In this regard, four types of FFP implementations will be discussed. Although different implementations of the FFP will not affect the steady-state frequency adaptation, their dynamical effects on the small-signal stability of SOGI-PLL/FLL remain concealed. To this end, this article will present a comprehensive stability assessment and comparative analysis of SOGI-PLL/FLL focusing on the FFP issue. To extend the applicability and accuracy of discussions, all the analyses will be fulfilled by using a parameter space-oriented stability assessment method formulated in the linear-time periodic (LTP) framework. The obtained results are verified by time-domain simulations, and the main findings are further interpreted by using appropriate analytical models.